Efforts to Improve Employee Performance Through Emotional Intelligence and Psychological Capital Mediated by Organizational Citizenship Behavior (OCB) (Case Study on Employees of PT BPR BKK Purwodadi (Perseroda) - Anita Fitriani Yusuf; Lie Liana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze efforts to improve employee performance through emotional intelligence and psychological capital mediated by organizational citizenship behavior (OCB). The population in this study was 332 employees of PT BPR BKK Purwodadi (Perseroda). The number of samples was 117, taken using the Roscoe formula (1975). Sampling used a purposive sampling technique with the criteria of employee service period of more than 1 year and employees in the operational section. Data were processed using SPSS software version 22. Data analysis techniques included respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, R2 tests, t tests, and path analysis tests. The results of the study stated that emotional intelligence had a positive effect on OCB, psychological capital had a positive effect on OCB, emotional intelligence had a positive effect on employee performance, psychological capital had a positive effect on employee performance, OCB had a positive effect on employee performance, OCB mediated the effect of emotional intelligence on employee performance, and OCB mediated the effect of psychological capital on employee performance.